Profil Kemampuan Numerasi Siswa Kelas VII MTs Negeri 7 Malang dalam Menyelesaikan Soal AKM - Mois, Fajrul Falah; Masamah, Ulfa; Putri Utami, Mutiara Arlisyah (Galois: Jurnal Penelitian Pendidikan Matematika, 2025)
This research aims to study students' level of numeracy skills in class VII F MTs Negeri 7 Malang through the analysis of Minimum Competency Assessment (AKM) questions. The qualitative descriptive method was used to examine the numeracy skills of students from low, medium, and high categories. Three students representing each numeracy ability category were selected using a purposive sampling technique. Data collection was done through AKM test questions and interviews. Data were analyzed through the stages of collection, condensation, presentation, and conclusion. The results showed that 34% of students had low numeracy skills, 33% had medium numeracy skills, and 33% had high numeracy skills. Interview analysis revealed that students with high numeracy were able to solve the problem accurately and consistently. Students with medium numeracy ability need additional guidance, while students with low numeracy ability have difficulty in understanding and applying mathematical concepts. This research recommends a comprehensive and integrated learning approach to improve students' numeracy skills. This approach should involve various aspects of the learning process to achieve optimal results. ABSTRAK Penelitian ini bertujuan untuk mempelajari tingkat kemampuan numerasi siswa kelas VII F MTs Negeri 7 Malang melalui analisis soal Asesmen Kompetensi Minimum (AKM). Metode deskriptif kualitatif digunakan untuk mengkaji kemampuan numerasi siswa dari kategori rendah, sedang, dan tinggi. Tiga siswa mewakili setiap kategori kemampuan numerasi dipilih dengan teknik purposive sampling. Pengumpulan data dilakukan melalui soal tes AKM dan wawancara. Data dianalisis melalui tahapan pengumpulan, kondensasi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa 34% siswa memiliki kemampuan numerasi rendah, 33% memiliki kemampuan numerasi sedang, dan 33% memiliki kemampuan numerasi tinggi. Analisis wawancara mengungkapkan bahwa siswa dengan kemampuan numerasi tinggi mampu menyelesaikan soal dengan akurat dan konsisten. Siswa dengan kemampuan numerasi sedang membutuhkan bimbingan tambahan, sedangkan siswa dengan kemampuan numerasi rendah mengalami kesulitan dalam memahami dan menerapkan konsep matematika. Penelitian ini merekomendasikan pendekatan pembelajaran yang menyeluruh dan terintegrasi untuk meningkatkan kemampuan numerasi siswa. Pendekatan ini harus melibatkan berbagai aspek proses pembelajaran untuk mencapai hasil yang optimal.